Le terrain : la fin d’un grand récit ? - Yann Calbérac (Bulletin de l’Association de Géographes Français)
Fieldwork – i.e collecting data outside – has been promoted, thanks to Paul Vidal de La Blache, as the main method of geographers. It appears as a metanarrative (according to the definition given by Jean-François Lyotard) insofar as it enables geography to reach modernity. The passionate debates dealing with fieldwork during the 1960s and the 1970s reveal the decrease of this metanarrative at that time: it is no longer play an important part in the community of French geographers.